The Effect of Leadership, Employee Engagement, and Work Environment on Employee Performance in the Manufacturing Industry - Joko Suyono; Aldrin Arizona Suyono; Damarsari Ratnasahara Elisabeth; Ahmad Zazuli; Sukaris Sukaris (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Employee performance is a strategic determinant for the sustainability and competitiveness of the organization, especially in the manufacturing industry that faces pressure on efficiency and production accuracy. This study aims to analyze the influence of leadership, employee engagement, and work environment on employee performance, both partially and simultaneously. The study used a quantitative approach by collecting data through a structured questionnaire given to all 66 permanent employees as respondents, so this study used a total sampling technique. The collected data were analyzed using multiple linear regression to test the relationships between variables. The results of the study show that leadership, employee engagement, and work environment each have a significant partial effect on employee performance, and simultaneously, these three variables are proven to have a significant influence on improving employee performance. These findings confirm that organizational effectiveness is largely determined by the synergy between a supportive leadership style, high employee engagement, and a conducive work environment. This research makes a theoretical contribution in strengthening the understanding of the determinants of employee performance in the context of the manufacturing industry and provides practical implications for company management in formulating performance improvement strategies through strengthening leadership, optimizing engagement, and improving the work environment.